Sustainable Rural Tourism: Kajian Potensi dan Dampak Desa Sukowilangun menuju Desa Wisata - Cahyaningsih, Diyah Sukanti; Tutuko, Pindo; Sufiyanto, Sufiyanto; Widayati, Sri (Universitas Tribhuwana Tunggadewi Malang, 2023)
This research is initial research that aims to provide direction for village assistance activities towards tourism villages within the framework of Sustainable Rural Tourism. Community development and empowerment form the basis of this activity. By prioritizing the wishes, hopes, and participation of the community, this research maps out the potential and impacts that can occur with the existence of a tourism village. From these potentials and impacts, researchers conducted a qualitative analysis by providing five alternative developments that could be carried out in assisting Sukowilangun Village to become a tourist village. Through one of the developmental approaches, a holistic approach, participatory learning, empowerment of management, action research, or synergy and network analysis, it is hoped that village servants or assistants towards sustainable tourism villages will have the direction of planning, implementing, and evaluating programs properly so that the concept of village development is within the framework of Sustainable Rural Tourism can be achieved. The results of this study have been applied to the early stages of community service, with a holistic approach, servants can map the main potential, namely culture. Culture is the main wealth and strength to be developed further in supporting natural and other potentials towards Tourism Villages.ABSTRAKKegiatan ini merupakan penelitian awal yang bertujuan memberikan arah bagi kegiatan pendampingan desa menuju desa wisata dalam kerangka Sustainable Rural Tourism. Pembangunan dan pemberdayaan masyarakat menjadi dasar kegiatan ini. Dengan mengutamakan keinginan, harapan dan partisipasi masyarakat, penelitian ini memetakan potensi dan dampak yang dapat terjadi dengan adanya desa wisata. Dari potensi dan dampak tersebut, peneliti melakukan analisi kualitatif dengan memberikan lima alternative pengembangan yang dapat dilakukan dalam mendampingi Desa Sukowilangun menuju Desa wisata. Melalui salah satu dari analisis pengembangan holistic approach, participatory learning, empowerment of management, action research, atau sinergy and network, diharapkan pengabdi atau pendamping desa menuju Desa Wisata berkelanjutan memiliki arah penetapan perencanaan, implementasi hingga evaluasi program dengan baik sehingga konsep pengembangan desa dalam kerangka Sustainable Rural Tourism dapat dicapai. Hasil penelitian ini telah diterapkan pada tahap awal pengabdian, dengan pendekatan holistic, pengabdi mampu memetakan potensi utama yaitu budaya. Budaya menjadi kekayaan dan kekuatan utama untuk dikembangkan lebih jauh dalam mendukung potensi alam dan lainnya menuju Desa Wisata.